A community"“wide trophic structure analysis in intertidal ecosystems on the south coast of South Africa - Gusha, Molline Natanah C (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2018)
Coastal ecosystems are more than microhabitats for marine species. Acting as atmospheric carbon filters, species in coastal environments are directly and/or indirectly associated with transferring organic carbon to species at higher trophic levels. However, the progressing change in global climatic conditions has created the need to assess the consequences of the shifting conditions on both direct and indirect interactions of physical and biological parameters at species and/or community levels. From these perturbations, the effects of biotic homogenization on ecosystem functioning and resilience can also be realised. Herein, I discuss the effects of temperature, nutrients, biotic interactions and habitat characteristics on community dynamics within intertidal rock pool systems on the south coast of South Africa using complementary qualitative and quantitative analytical methods. Seasonality had a significant impact on rock pool species with changes in composition and higher richness in winter than summer. The first two axes of the Canonical Correspondence Analysis (CCA) of the plant and animal communities each explained ~20% of the relationship between physico-chemical parameters and biological variables. The CCA highlighted that seasonal shifts in chlorophyll-a, conductivity, salinity, water depth, surface area and substratum type indirectly influenced species composition. For example, pools with heterogenous substratum comprising a mixture of sand and rock exhibited higher species diversity than homogenously bedded pools. Furthermore, a Bayesian analysis of community structure based on stable isotope ratios was used to assess how trophic pathways of carbon and nitrogen elements reflected community composition and richness. Isotopic biplots showed an increase in food web size, food chain length and the trophic positions of fish and some gastropods in winter compared to summer. There was greater dietary overlap among species in larger pools. In addition, while isotopic nearest neighbour distance and species evenness also showed a positive increase with pool size in summer, the same metrics were almost constant across all pool sizes in winter. These changes in food web packing and species evenness suggest seasonal preferences or migration of species in summer from small pools to larger pools with stable physico-chemical parameters. Furthermore, the presence of fish was seen to promote trophic diversity within some pools. The results from laboratory microcosm grazing experiments demonstrated significant direct and indirect effects of temperature and nutrients within plankton communities. Copepod grazing had an indirect positive influence on phytoplankton biomass and size structure while the interactive effects of temperature and nutrients had contrasting effects on both phytoplankton communities and copepod biomass. Shifts in water chemistry and nutrient treatments were also observed in the presence of copepods. Phosphate addition had a recognisable impact on plankton communities. The presented synthesis of the literature mainly highlighted that positive effects at one trophic level do not always positively cascade into the next trophic level which is evidence of complex interactive biotic, habitat and water chemistry effects within these intertidal ecosystems. Thus, to further understand cascading effects or community structure functioning in general, there may be a need to incorporate and understand species functional traits and how they contribute to trophic diversity, community restructuring and functioning in coastal habitats.
Keywords: Food chains (Ecology); Coastal ecology -- South Africa; Intertidal ecology -- South Africa; Marine animals -- Climatic factors -- South Africa; Marine animals -- Food -- South Africa; Marine animals -- Habitat -- South Africa